(untitled) (Swiss Medical Weekly, 2016)
PRINCIPLES: The HOSPITAL score is a simple prediction model that accurately identifies patients at high risk of readmission and showed good performance in an international multicentre retrospective study. We aimed to demonstrate prospectively its accuracy to predict 30-day unplanned readmission and death. METHODS: We prospectively screened all consecutive patients aged ≥50 years admitted to the department of general internal medicine of a large community hospital in Switzerland. We excluded patients who refused to give consent, who died during hospitalisation, or who were transferred to another acute care, rehabilitation or palliative care facility. The primary outcome was the first unplanned readmission or death within 30 days after discharge. Some of the predictors of the original score (discharge from an oncology service and length of stay) were adapted according to the setting for practical reasons, before the start of patient inclusion. We also assessed a simplified version of the score, without the variable “any procedure performed during hospitalisation”. The performance of the score was evaluated according to its overall accuracy (Brier score), its discriminatory power (C-statistic), and its calibration (Hosmer-Lemeshow goodness-of-fit test). RESULTS: Among the 346 included patients, 40 (11.6%) had a 30-day unplanned readmission or death. The HOSPITAL score showed very good accuracy (Brier score 0.10), good discriminatory power (C-statistic 0.70, 95% confidence interval [CI] 0.62–0.79), and an excellent calibration (p = 0.77). Patients were classified into three risk categories for the primary outcome: low (59%), intermediate (20.8%) and high risk (20.2%). The estimated risks of unplanned readmission/death for each category were 8.2%, 11.3% and 21.6%, respectively. The simplified score showed the same performance, with a Brier score of 0.10, a C-statistic of 0.70 (95% CI 0.61–0.79), and a goodness-of-fit statistic of 0.40. CONCLUSIONS: The HOSPITAL score prospectively identified patients at high risk of 30-day unplanned readmission or death with good performance in medical patients in Switzerland. Its simplicity and good performance make it an easy-to-use tool to target patients who might most benefit from intensive transitional care interventions.